Tissue engineering in female pelvic floor reconstruction. Issue 7 (14th April 2020) - Wu, Xiaotong; Jia, YuanYuan; Sun, Xiuli; Wang, Jianliu
Abstract: Pelvic organ prolapse is a common and frequently occurring disease in middle‐aged and elderly women. Mesh implantation is an ideal surgical treatment. The polypropylene mesh commonly used in clinical practice has good mechanical properties, but there are long‐term complications. The application of tissue engineering technology in the treatment of pelvic organ prolapse disease can not only meet the mechanical requirements of pelvic floor support, but also be more biocompatible than traditional polypropylene mesh, and can promote tissue repair to a certain extent. In this paper, the progress of tissue engineering was summarized to understand the application of tissue engineering in the treatment of pelvic organ prolapse disease and will help in research.